Knowledge and awareness on Hepatitis B and C Infection among antenatal women attending a government hospital in Delhi: A Cross-sectional study - Singh, Suniti; Kumar, Rajesh; TP, Sherin Raj (Indian Journal of Community Health, 2025)
Background: Pregnant women with chronic Hepatitis B and positive Hepatitis B virus E antigen (HBeAg) have a 90% likelihood of transmitting the hepatitis B virus to their newborns. Vertical transmission is the leading cause of HCV infection in children. Hepatitis B and C lead to chronic disease and are the most common cause of liver cirrhosis, liver cancer, and viral hepatitis-related deaths. A major challenge to eliminating viral Hepatitis can be a lack of awareness regarding infection. Aims & Objective: To study the level of knowledge and awareness on Hepatitis B and C infection among antenatal women attending a government hospital in Delhi. Methodology: A cross-sectional, descriptive study was conducted in Delhi amongst 422 antenatal women. Participants were interviewed using a semi-structured interview schedule. To assess knowledge a composite variable of knowledge score was generated, and the cut-off score of 7/14 was kept. Results: Among the interviewed pregnant women, only 47(11.1%) were aware of either Hepatitis B or both Hepatitis B and C, and among these, only 19.1% had adequate knowledge. Conclusion: Pregnant women showed a low level of awareness, indicating a pressing need for education and awareness campaigns.